PENGARUH MESSAGE FRAMING DAN KREDIBILITAS SUMBER DALAM KAMPANYE SAFETY RIDING (PENDEKATAN SOSIAL MARKETING) - Ulvi Dino Vita (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to determine the effect of message framing and source credibility on attitudes and intentions of driving in safety riding. The type of research is experimental research. This research uses the 2x2 factorial design. This study uses four different combinations of posters as experimental stimuli. Participants in this study were 120 people who can drive two wheels vehicle and were willing to participate in the experiment. Primary data were collected through questionnaires. The result of this study shows that the message framing creates a positive effect on the attitude and intention of driving in safety riding. The source credibility also gives a positive influence on attitude and intentions of driving in safety riding. There is interaction between message framing and source credibility to driving attitude is safety riding. However, there is no interaction between message framing and source credibility on intentions drive in safety riding. Therefore, it is important for a social marketer to pay attention to the message framing and choosing the credible source in a campaign in order to influence the attitude and intention of the audience positively. Keywords : message framing, source creadibility, attitude, behavioral intention, safety riding